Fabrication of novel particleboards from oil palm frond blended with empty fruit bunch and treated with preservative against termite - Wahida, Amat Fadzil (2017)
The shortage of forest resources has triggered an increase in awareness among the wood based product industry to find alternative supply of raw materials for composites production. Currently, oil palm biomass is undergoing research and development and appears to be the feasible alternative to the wood shortage problem. In this research, novel blend particleboards made of oil palm fronds (OPF) particles and empty fruit bunch (EFB) fibre were successfully fabricated. A Box-Behnken experimental design was carried out to determine the effects of pressing temperature, pressing time and EFB/OPF ratio on the properties of the OPF particleboards. Three levels were employed for each variable. The responses are modulus of rupture (MOR), modulus of elasticity (MOE), internal bonding (IB), water absorption (WA) and thickness swelling (TS) of fabricated particleboards were analysed using Design Expert Software. Model simulation and numerical optimisation were also carried out. The statistical analysis showed that all the variables have significant effects on the properties of particleboards. The optimised parameters for maximum MOR, MOE and IB, and minimum WA and TS determined were found to be: press temperature, 186 °C; press time, 5.70 min; and EFB/OPF ratio, 30.4%. A treatment of optimised OPF-EFB particleboards with various concentrations of cypermethrin (0.5, 1.0 and 1.5% w/v) and neem oil solution (5, 10 and 15% v/v) has been used to improve the resistance of fabricated particleboard against termite. Termite resistance of particleboards sample was evaluated in two ways; laboratory test and field test. The finding from both tests revealed that the OPF-EFB particleboards treated with cypermethrin and neem oil has improved the resistance of particleboards against termite.